Single nucleotide polymorphisms associated with benzimidazole resistance of the β-tubulin isotype 1 gene in Ascaris lumbricoides isolated in South Africa - Teniel Ramkhelawan; Pragalathan Naidoo; Zilungile L. Mkhize-Kwitshana (Brazilian Journal of Infectious Diseases)
Background: Ascariasis is a parasitic infection caused by Ascaris lumbricoides and infects over 1.2 billion people worldwide. Benzimidazole (BZ) drugs remain the standard treatment in large-scale deworming programs globally. The prevalence of Single Nucleotide Polymorphisms (SNPs) in the β-tubulin gene of A. lumbricoides (F200Y, E198A and F167Y) is increasing due to the widespread use of BZ drugs. Aim: To investigate the prevalence of the above-mentioned SNPs in a South African adult population. Methods: This was a sub-study of the main cross-sectional study with participants (n = 414) who had been recruited from five public health clinics in the peri‑urban areas South of Durban, KwaZulu-Natal, South Africa. For the current study, a purposive selection of 20 stool samples that were positive for A. lumbricoides eggs was made. A. lumbricoides worm extracts (n = 4) were used as a positive control. Sanger sequencing and RFLP-PCR were used to identify the presence of mutations. Results: No mutations were detected, and all genotypes observed at codons F167Y, E198A and F200Y were the homozygous wild-type genotype. Conclusion: Although no mutations were found in this small study, the potential occurrence of mutations in a larger sample subset cannot be ruled out.